Digital inequality and intergenerational solidarity: The role of social support in proxy internet use - Dolničar, Vesna; Filipović Hrast, Maša; Vehovar, Vasja; Petrovčič, Andraž (AoIR Selected Papers of Internet Research, 2013)
The digital divide research has recently documented a set of new practices related to people’s internet use that put the binary division between internet users and non-users under question. Especially, among the elderly population a considerably large group of proxy internet users has been identified who do not use the internet by themselves, but rather ask members of their personal networks to do things online for them. As proxy internet users rely mainly on their children and/or grandchildren, who play the role of warm experts, this paper suggests that the notion of intergenerational solidarity might be a sound conceptual basis to understand the under-researched relationship between social support and digital inequality. On the empirical level, this paper explores how the availability and lack of different types of social networks and their characteristics is associated with proxy use and non-use of internet. The results of multivariate analysis on survey data from a nation-wide representative sample show that between emotional and socializing support only the latter is associated with proxy internet use: internet non-users with larger socializing networks and stronger intergenerational support (e.g., a higher proportion of (grand)children) are more likely to be proxy internet users. Findings also indicate that younger internet non-users with higher education and children are more inclined to be proxy internet users.